The postcolonial studies dictionary - Nayar, Pramod K. (Hoboken : Wiley, 2015)
'The Post colonial Studies Dictionary provides students with an essential resource for navigating the field of post colonial theory'--
Sublime (as colonial aesthetic)syncretism; T; terra incognita; terra nullius; testimonio; text/textuality (colonial); Third World; torrid zones; transculturation; transnationalism; tricontinentalism; tropicality; U; universalism; V; vernacular; W; whiteness/white studies; World Literature; worlding; References; End User License Agreement
Includes bibliographical references.
Print version record and CIP data provided by publisher.
Keywords: 1900-2099; Postcolonialism in literature -- Dictionaries; Postcolonialism -- Dictionaries; Literature, Modern -- 20th century -- Dictionaries; Literature, Modern -- 21st century -- Dictionaries; Literary criticism; LITERARY CRITICISM -- Semiotics & Theory; Literature; Literature, Modern; Postcolonialism; Postcolonialism in literature; Developing countries -- Literatures -- Dictionaries; Developing countries; Electronic books; Dictionaries